Understanding the experiences of ketogenic metabolic therapy for people living with varying levels of depressive symptoms: a thematic analysis - Bellamy, Erin L.; Hadjiefthyvoulou, Florentia; Walsh, James; Brown, Jennie; Turner, John (Frontiers in Nutrition, 2024)
Background: Evidence suggests that a ketogenic diet (KD) may help to alleviate psychiatric symptoms, including depression and anxiety. Positive changes have been reported such as improvements in cognition, concentration, and sleep, a reduction in hunger, and an increase in wellbeing, energy, confidence, and resilience. This research aims to understand the impact of a noncalorie-restricted KD on depression and aspects of psychological well-being in those with varying degrees of depressive symptoms. Though there are a few studies directly exploring the experiences of those following a KD, this will be the first study to explore the narrative from a mental health and psychological well-being viewpoint.Method: A sample of nine participants who had followed a non-calorie restricted KD intervention of 50g of carbohydrates or less per day for at least 12 weeks were recruited. Participants were split into 'healthy adults' group who had no to low depressive symptoms and 'depressive symptoms' group who had mild to moderate depressive symptoms. A reflexive thematic analysis was considered suitable for this study.Findings: Five core themes and 24 subthemes were created. These were, (1) Poor health prior to program; (2) Hunger and cravings -the food and mood connection; (3) Psychological well-being improvements; (4) It becomes a lifestyle; and (5) Implementation difficulties. Participants experienced mental health improvements such as increased self-esteem, confidence, motivation, and achievement. Some experienced more control in life and a greater sense of reward. Those with depressive symptoms who initially reported low self-worth and hopelessness later reported increased self-esteem and renewed meaning and purpose in life. The findings from this study reflect the previous reports that the diet implementation can be difficult initially, but soon becomes easy to follow and turns into a lifestyle. Conclusion: In the literature, there are very few qualitative studies that explore the accounts and lived experiences of those following a KD. From the participants' accounts in this study, it appears that the benefits and positive outcomes of this diet outweigh any negative side-effects experienced. This is encouraging for those who are looking for adjunctive therapies to address and improve their depressive symptoms and overall mental health.